Sosialisasi Pengenalan Formula Array pada Excel untuk Siswa Siswi SMA 1 Gunung Talang Solok - Rahman, Sepsa Nur; Nozomi, Irohito; Surmayanti, Surmayanti (Jurnal Pengabdian Masyarakat Dharma Andalas, 2024)
This Community Service aims to socialize the introduction of array formulas in Excel to SMA 1 Gunung Talang Solok students. Array formulas are a very useful feature in data processing in Excel, but are often not widely known by high school students. The method used in this research is a socialization method which involves presentations, demonstrations, and direct practice using array formulas in Excel. Socialization was carried out in the form of training involving SMA 1 Gunung Talang Solok students. The research results showed that the socialization of the introduction of array formulas in Excel had a positive impact on students at SMA 1 Gunung Talang Solok. After following the socialization, students were able to understand and apply array formulas in data processing in Excel. They are able to create array formulas that are more efficient and accurate in completing tasks that involve data processing